Probiotics in the Mechanism of Protection Against Gut Inflammation and Therapy of Gastrointestinal Disorders - Dylag, Katarzyna; Hubalewska-Mazgaj, Magdalena; Surmiak, Marcin; Szmyd, Jakub; Brzozowski, Tomasz (Current Pharmaceutical Design, 2014)
A growing body of experimental and clinical evidence supports the hypothesis that the intestinal microbiota markedly influences function and the structure of the mucosal lining. Intestinal microbiota can potentially cause damage to the mucosa either directly by releasing toxins or indirectly by causing a detrimental immune response. Probiotic bacteria have been defined as live microorganisms, which when consumed in adequate amounts, confer a health benefit for the host. In recent years, the therapeutic and preventive application of probiotics for several gastrointestinal and liver disorders has received increasing attention. Probiotics appear to be beneficial for premature infants who suffer necrotizing enterocolitis. The effectiveness of certain probiotics as treatment for infectious and antibioticassociated diarrhea in adults and for allergic disorders in children has been supported by clinical studies; however, the potential mechanism( s) remains to be studied. Experimental studies and clinical trials for probiotic treatment of inflammatory bowel diseases (IBD) have yielded conflicting results. Daily intake of selected probiotics was effective in the prevention of ulcerative colitis and the attenuation of the active onset of Crohn’s disease or ulcerative colitis but others failed to show a beneficial effect. The combination of Lactobacillus, Bifidobacterium, Saccharomyces boulardi and the treatment with Escherichia coli Nissle were found beneficial in inducing and maintaining remission of disease activity of gut inflammation and moderately severe ulcerative colitis. Probiotic bacteria were considered in some studies as a safe adjuvant when added to triple eradication therapy against the symptoms induced by the major gastric pathogen, Helicobacter pylori. This review attempted to overview these new exciting advances in the role of these microbes in the pathogenesis, management and treatment of gastrointestinal disorders.
Keywords: Helicobacter pylori